Asymmetrical dimethylarginine regulates endothelial function in methionine-induced but not in chronic homocystinemia in humans: effect of oxidative stress and proinflammatory cytokines. - Antoniades, C; Tousoulis, D; Marinou, K; Vasiliadou, C; Tentolouris, C; Bouras, G; Pitsavos, C; Stefanadis, C (2006)
BACKGROUND: Homocystinemia is a metabolic abnormality associated with endothelial dysfunction and increased cardiovascular disease risk. The underlying mechanisms of these effects, however, are obscure. OBJECTIVE: We examined the effect of asymmetrical dimethylarginine (ADMA) on endothelial dysfunction in methionine-induced and chronic homocystinemia and evaluated the regulatory role of oxidative stress and proinflammatory cytokines on the release of ADMA. DESIGN: In this double-blind, placebo-controlled parallel group study, 30 subjects of both sexes (15 with homocystinemia and 15 healthy controls) underwent methionine loading, with simultaneous administration of a combination of vitamin C (2 g) plus alpha-tocopherol (800 IU) or placebo. Endothelial function in forearm resistance vessels and concentrations of ADMA, oxidized LDL, and proinflammatory cytokines were determined at baseline and 4 h after methionine loading. RESULTS: Both chronic and methionine-induced homocystinemia were associated with increased oxidized LDL (P < 0.01), higher expression of the proinflammatory cytokine interleukin 6 (P < 0.05), and endothelial dysfunction (P < 0.01). Although ADMA rapidly increased in acute homocystinemia (P < 0.01) and was correlated with forearm hyperemic response at 4 h after methionine loading (r = -0.722, P = 0.0001), it was not higher in subjects with high versus low fasting homocysteine. High-dose antioxidant treatment prevented methionine-induced elevation of oxidized LDL and interleukin 6 but failed to prevent the increase in ADMA or endothelial dysfunction. CONCLUSIONS: Both chronic and methionine-induced homocystinemia are characterized by increased oxidative stress and proinflammatory cytokines, which may contribute to the development of endothelial dysfunction. However, the ADMA pathway is activated only in acute homocystinemia by mechanisms not mediated by oxidized LDL or proinflammatory stimuli.